Tourism development policy and planning
"It has been noted that tourism has always been a priority for governments, and this is reflected in research on tourism policy, despite being a relatively new phenomenon. It is very common for tourism policy to be considered as an economic policy, but tourism is much more than that. Tourism has significant impact on our societies, and it will continue to be one of our top concerns in the future. With the goal of achieving a variety of tourism-related objectives, tourism policies are set of discourses, decisions, and practices develop by governments and collaboration with private and social actors. Studies on sustainable tourism policy have gained increasing attention in recent years. Tourism policy practice and tourism research have widely recognized sustainable tourism after more than three decades of development. Sustainable tourism policy stakeholders, implementation of sustainability policies, climate policy, indicators of sustainable tourism, and the role as sustainable tourism policy. Through the development and implementation of sustainable tourism policies, global environmental and sustainable development challenges can be effectively addressed. The book contains seven chapters which examine the differences between sustainable tourism policy and sustainable development policy." --